IMPROVING THE INTEGRATION OF INSURANCE COMPANIES AND COMMERCIAL BANKS - Kenjayev Ilhom Giyozovich; Ganiev Shahriddin Vokhidovich (Journals Park Publishing, 2023)
The article presents the economic essence of the process of integration of insurance companies and commercial banks, their classification, and analysis of mutual cooperation between insurance companies and commercial banks. The advantages of cooperation between insurance companies and commercial banks, as well as the classification criteria for bancassurance and international legal norms were also studied.
Keywords: insurance companies, commercial banks, integration process, bancassurance, insurance premiums, insurance payments, insurance money, insurance liability, insurance events, insurance contracts, investment activities of.